New associations of classic acute macular neuroretinopathy. Issue 3 (20th August 2015) - Munk, Marion R; Jampol, Lee M; Cunha Souza, Eduardo; de Andrade, Gabriel Costa; Esmaili, Daniel D; Sarraf, David; Fawzi, Amani A
Abstract : Purpose: To describe novel underlying associations of classic acute macular neuroretinopathy (AMN). Methods: Multimodal imaging case series evaluating patients with classic AMN lesions and previously unreported underlying aetiologies. Results: Six patients were included (five women, one man, mean age 30±7 years). Mean distance best corrected visual acuity at initial presentation was 0.21±0.3 logMAR (mean Snellen acuity: 20/30, range 20/15–20/100) and at last follow-up visit 0.09±0.17 logMAR (Snellen acuity: 20/20, range 20/15–20/60). All cases but one had bilateral lesions and showed typical parafoveal hyporeflective lesions on infrared imaging, which corresponded to the hyper-reflectivity in the Henle's layer with attenuation of the external limiting membrane, the ellipsoid zone and interdigitation zone. Underlying diseases included thrombocytopenia and anaemia associated with dengue fever, acute lymphoblastic leukaemia, chronic kidney disease and ulcerative colitis, while Valsalva-like manoeuvre was found to be a potential trigger. Other novel associations included the use of lisdexamphetamine. Conclusions: Classic AMN may be associated with leukaemia, dengue fever, ulcerative colitis and chronic kidney disease, probably as a result of chorioretinal hypoxia in the setting of thrombocytopenia and anaemia. Adrenergic agonists such as lisdexamphetamine may also contribute to the manifestation of AMN.